Beyond databases, architectures and structures: towards efficient solutions for data analysis and knowledge representation : 13th international conference, BDAS 2017, Ustron, Poland, May 30 - June 2, 2017, proceedings /: 13th international conference, BDAS 2017, Ustron, Poland, May 30 - June 2, 2017, proceedings. (2017) - Unknown
No abstract available